Disentangling anti-corruption agencies and accounting for their ineffectiveness - Krambia-Kapardis, Maria (My University, 2019)
Purpose: The purpose of this paper is to provide an adequate account of anti-corruption agency (ACA) ineffectiveness and propose the kind of ACA that would hold the promise of success. The paper draws on legitimacy theory, legal process and the notion of integrity of purpose. Design/methodology/approach: This paper contextualizes the establishment and proliferation of ACAs; explores different ways of conceptualizing them; examines the broad range of factors that have underpinned ACA ineffectiveness and utilizes both legitimacy theory and the notion of the integrity of purpose. Findings: The one-ACA-model-fits-all approach in corruption-control has been an abysmal failure. Disentangling the reasons for ACA ineffectiveness reveals various endogenous and exogenous factors. It also emphasizes the crucial importance of integrating both legitimacy theory and integrity of purpose in a revamped ACA concept that meets the corruption-control challenge. Practical implications: It is possible to design and implement an effective ACA by avoiding various factors that have been shown to seriously undermine corruption control efforts by also drawing on legitimacy theory, legal process and integrity of purpose. Social implications: Corruption in both the public and private sectors cannot be controlled in isolation from other socio-economic problems. An effective ACA is one that fosters integrity and is considered legitimate by its stakeholders. Originality/value: While there have been some articles the past two decades discussing the effectiveness of ACAs in particular countries, this is the first paper to account for the overall ACA ineffectiveness also using legitimacy theory, legal process and integrity of purpose to revamp the ACA concept.
Keywords: Anti-corruption agencies; Effectiveness; Integrity; Legitimacy theory